INDONESIA’S INTEREST IN BUILDING MILITARY COOPERATION WITH TIONGKOK IN PRODUCING THE C-705 MISSILE - Meina Rizki Amalia; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aimed to describe why Indonesia agreed cooperating with Tiongkok in producing the C-705 missile. This research explain what are the Indonesia’s interest and what are Indonesia’s goals from this cooperation. The cooperation consist in four steps, there are Semi Knock Down, Complete Knock Down, Production, and Research and Development.Researcher analyzed this case using qualitative methods to find data and facts through some literature. The literature collected from books, journals, mass media and websites. Researcher use neorealism perspective which believe that international system is anarchy, cooperation build up to maximize the power of the country to survive in the anarchy situation. The level analysis of the research is nation-state and also use international cooperation theory by Kalevi Jaakko Holsti.From this research it can be seen, Indonesia choose Tiongkok as a partner in producing the C-705 missile because of the Indonesia’s needs toward high technological weapon to increase the Indonesia’s military industry. Military indutsry cooperation made a major impact on changes in military technology by the armed forces of the Republic of Indonesia, mainly on the strenght of the naval defense equipment dimensions.Keywords: International Cooperation, Minimum Essential Force, C-705 Missile